How dangerous is a Drosera? Limb autotomy increases passive predation risk in crickets - Cross, Adam; Bateman, Bill (Wiley-Blackwell, 2018)
© 2018 The Zoological Society of London Autotomy, the voluntary shedding of body parts, is a strategy employed by many organisms to evade predation and escape entanglement. Although this strategy may allow an individual to survive one threat encounter it can come at significant cost, with studies indicating that autotomized individuals exhibit reduced fitness and increased susceptibility to active predators. However, little is known about the interplay between autotomy state and passive predation risk. We explored this interaction experimentally using prey of different size and autotomy state (laboratory-raised crickets) exposed to a sessile predator (the carnivorous plant Drosera collina). Data indicated a strong relationship between capture likelihood and autotomy state, with capture likelihood increasing from 6% in intact crickets (those retaining both hind legs) to 31% in single autotomized and 44% in double autotomized individuals. A weaker, though still strong, relationship was observed between capture likelihood and prey size, with smaller crickets (7–32 mg) paying a markedly greater cost for limb loss than larger crickets (100–280 mg). Capture likelihood for small crickets after single- or double-autotomy was increased by 56 and 72% respectively compared to intact individuals, while this risk only increased by 2 and 13% respectively for large crickets. Our results further highlight the costs of autotomy to fitness and the long-term survival of individuals, suggesting not only that this strategy may markedly increase the susceptibility of organisms to future passive predation but also that the cost is higher for earlier ontogenetic stages.